Poly(indole-6-carboxylic acid) and tetracyanoquinodimethane-modified electrode for selective oxidation of dopamine - Pandey P.C.; Chauhan D.S.; Singh V. (My University, 2025)
Poly(indole-6-carboxylic acid) (PICA) was synthesized electrochemically over glassy carbon electrode (GCE) through potentiodynamic mode of polymerization. The resulting polymer was soluble in Tris-HCl buffer (pH 7.0). The processable polymer was cast over desired electrode surface along with organic redox mediator tetracyanoquinodimethane (TCNQ) as an electron transfer relay using Nafion®. Nafion® was used to solubilize TCNQ as well as to introduce permselectivity to the blend of polymer and TCNQ. The above blend was cast over GCE and characterized by cyclic voltammetry followed by its application in electrochemical sensing of dopamine (DA) and ascorbic acid (AA). The modified electrode was found to be selective for DA analysis. The lowest detection limit of DA sensing was found to be 4 μM{cyrillic} with a sensitivity of 18 μA ± 6 nA/mM of DA. © 2008 Elsevier Ltd. All rights reserved.